MUSLIM DIASPORIC IDENTITIES IN KAMILA SHAMSIE’S HOME FIRE (2017) - Rivaldy, Padel Muhamad Rallie; Budiman, Manneke; Tambunan, Shuri M. Gietty (International Review of Humanities Studies, 2019)
Beside accepted with surprise across the world, the winning of Brexit referendum also brings up the tangled web into the United Kingdom’s political and cultural realms. Recent studies mention there is correlation between the voting behavior and issues of identity, immigration, and Islamophobia. Kamila Shamsie alludes these issues in her latest novel, Home Fire (2017). By focusing on three main protagonists, this close-textual analysis examines how Pakistani diasporic community construct their identities within the novel. To support the analysis, this article draws upon Hall’s identity theory (1990) and Bhabha’s Unhomely (1992). Research findings show how Shamsie’s novel represents heterogeneity within Pakistani Muslims diasporic identities, rather than frame them within single collective identity. Therefore, the novel criticizes Eurocentric biases point of view by portraying Muslim female protagonists’ fluid identities while defending their Muslimness by using veil and praying to God. On the other hand, the novel maintains established stereotype by drawing Muslim male protagonist’s affiliation with Daesh as representation of radical group to problematize the notion of radicalism.